Classification of myasthenia gravis and congenital myasthenic syndromes in dogs and cats. (15th July 2020) - Mignan, Thomas; Targett, Mike; Lowrie, Mark
Abstract: Myasthenia, a syndrome of impaired neuromuscular transmission, occurs as either an acquired or congenital condition. Myasthenia gravis (MG) is an acquired autoimmune disorder with autoantibodies against the neuromuscular junction (NMJ) of skeletal muscle whereas congenital myasthenic syndromes (CMSs) are a clinically heterogeneous group of genetic disorders affecting the NMJ with a young age of onset. Both conditions are diseases for which recognition is important with regard to treatment and outcome. We review the published literature on MG and CMSs in dogs and cats, and by comparison with published classification used in humans, propose a classification system for MG and CMSs in dogs and cats. Myasthenia gravis is first classified based on focal, generalized, or acute fulminating presentation. It then is subclassified according to the autoimmune disease mechanism or seronegativity. Autoimmune disease mechanism relates to the presence or absence of a thymoma, or administration of thiourylene medication in cats. Congenital myasthenic syndromes are classified according to the affected NMJ component, the mechanism of the defect of neuromuscular transmission, the affected protein, and ultimately the mutated gene responsible. In proposing this categorization of MG and CMSs, we hope to aid recognition of the disease groups for both conditions, as well as guide treatment, refine prognosis, and provide a framework for additional studies of these conditions.